Reversible Techniques of Ruffian in Sheep (Ovis aires) - Valle, Matheus Dias; Soutelino, Maria Eduarda Marques; Rocha, Letícia Ramos; Arashiro, Eduardo Kenji Nunes; Pereira, Gabriela Oliveira; Chenard, Marina Galindo; Feres, Catharine Porto; Carvalho, Vivian de Assunção Nogueira; Caldas, Saulo Andrade; Helayel, Michel Abdalla (Acta Scientiae Veterinariae, 2020)
Background: The use of teaser rams is an essential practice for detecting estrus in ewes as well as for accelerating puberty and synchronizing ovulation in the animal. There are several methods for preparing teasers, and the method used should be based on an assessment of the producer’s requirements. The ideal technique should be low cost and safe, ensuring the non-fertilization of ewes. This study evaluated the feasibility and effectiveness of two reversible teaser preparation techniques using a reversible plastic clamp. The techniques were compared in terms of functionality, possible post-surgical complications, and hematological changes of the rams as well as durability and reversibility. Materials, Methods & Results: Twelve healthy rams, aged 14-20 months, were divided into two groups (G1 and G2). Blood samples were collected through the jugular vein to perform the following analyses: blood count, total plasma protein, and fibrinogen. Following local infiltrative anesthesia with 5.0 mL 2% lidocaine without vasoconstrictor, the procedure was performed as follows: in G1, the preputial ostium was partially closed, and in G2, sigmoid flexure was performed in the cranial region, approximately 5-8 cm immediately caudal to the scrotal sac. In the postoperative period, 20 mg/kg oxytetracycline and 2.2 mg/kg flunixinmeglumine were intramuscularly administered as a single dose. The wounds were dressed, sprayed with repellent, and allowed to heal for seven days. The procedures in both groups were simple to perform, low cost, and low risk; caused minimal tissue injury; enabled rapid recovery; promoted little or no stress to the animals; are reversible; and left no complications. The animals of both groups satisfactorily identified the females in estrus during the three-month experimental period, maintained libido, and failed to mate with any female. The blood count levels remained within normal range in both groups evaluated at different time intervals. Hyperfibrinogenemia was observed in four animals of G1 and in three animals of G2 at T2, with a mean level of 600 mg/dL. However, the values returned to normal at T3 in both G1 and G2, when the mean observed fibrinogen level was 400 mg/dL. Discussion: Since these are simple, rapid procedures with low tissue injury and a simple anesthetic protocol, the animals showed rapid recovery, without intra or postoperative complications, enabling the immediate initiation of work. The techniques, therefore, demonstrate several advantages over the other techniques described above. It is estimated that the techniques used in this study are more economically viable than other techniques described in the literature, which require medium to high complexity procedures and long postoperative treatments and carry the risk of affecting the animal’s libido, making the animal unviable and more liable to be disposed. However, disposing of such animals represents great losses, as it interferes with the reproductive management and pregnancy of several females on the farm. In addition, the conventional techniques are irreversible, which means that these animals cannot be used for other purposes. The reversible techniques presented in this study allowed the teasers to successfully identify females in heat without mating with them because there was no exteriorization of the penis. The results of the blood count confirm that the procedures did not generate extensive tissue lesions, stress, pain, inflammation, or infection.